Calendar-life versus cycle-life aging of lithium-ion cells with silicon-graphite composite electrodes. (1st August 2018) - Kalaga, Kaushik; Rodrigues, Marco-Tulio F.; Trask, Stephen E.; Shkrob, Ilya A.; Abraham, Daniel P.
Abstract: The use of blended silicon-graphite (Si-Gr) negative electrodes increases the energy density of lithium-ion cells over those containing only graphite (Gr) electrodes. However, volume changes in the Si particles that occur during cycling cause deterioration of the solid-electrolyte interphase (SEI) layer on the particles resulting in further electrolyte reduction that immobilizes Li + ions and, therefore, capacity fade. Because the volume changes are not expected to occur during a potentiostatic hold (referred to as calendar-life aging), by comparison of cycle-life and calendar-life aged cells one can expect to assess the role of volume changes in the deterioration of cell performance. To this end, cells with Si-Gr and Gr negative electrodes (and Li1.03 (Ni0.5 Co0.2 Mn0.3 )0.97 O2 containing positive electrodes) were assembled, tested, and compared using cycle-life and calendar-life aging protocols. As expected, the capacity loss of the cycle-life aged cells was higher than that of the calendar-life aged cells. However, the measurable capacity loss for the calendar-life aged cells indicates continued immobilization of Li + ions. Furthermore, electrolytes extracted from the calendar-life aged cells showed more LiPF6 hydrolysis products than those extracted from the cycle-life aged cells. We discuss possible mechanistic causes for the observed aging behaviors in this article.